(untitled) (Journal of Food and Dietetics Research, 2021)
Objectives: Panai Olai Kozhukattai (POK) or simply palm leaf dumpling is a traditional south Indian delicacy which is very much popular in Tamil Nadu, India. POK preparation by traditional methods involves mixing all the ingredients to form a thick paste, which is then wrapped in tender palm leaf strips and cooked using steam under pressure. The present paper is the first-ever attempt on studying the nutritional characteristics of POK. Material and Methods: The nutritional analysis of POK involves proximate analysis, and vitamin and mineral composition. Results: The proximate analysis results demonstrated that POK is nutritionally predominant over the other South Indian breakfast foods. High levels of fat-soluble vitamins were present in POK. Water-soluble vitamins including niacin, pyridoxine, thiamine, and riboflavin were found in POK and with a high percentage of riboflavin. Among the mineral elements analyzed, the concentration of potassium in POK sample was the highest followed by magnesium, phosphorous, manganese, zinc, iron, and selenium. The study also documented a protocol of POK preparation. It is believed that the steaming in the palm leaves gives the palm leaf flavor to POK and it also transfers phytonutrients into the product from the palm leaves. Hence, the paper also focuses on investigating the presence of essential bioactive compounds in POK using qualitative phytochemical tests. The phytochemical screening of methanol extracts of POK revealed the presence of certain phytochemicals such as flavonoids, alkaloids, glycosides, and saponins and total flavonoid content of POK was estimated to be 148.25 mg/100 g. Conclusion: Overall, the study leads to the documentation of a preparation protocol along with the nutritional and phytochemical aspects of traditional POK with a view to promoting its consumption in other parts of the world.